A novel mechanism of soluble HLA-G mediated immune modulation: downregulation of T cell chemokine receptor expression and impairment of chemotaxis. - Fabio Morandi (Public Library of Science (PLoS), 2010)
Background In recent years, many immunoregulatory functions have been ascribed to soluble HLA-G (sHLA-G). Since chemotaxis is crucial for an efficient immune response, we have investigated for the first time the effects of sHLA-G on chemokine receptor expression and function in different human T cell populations. Methodology/principal findings T cell populations isolated from peripheral blood were stimulated in the presence or absence of sHLA-G. Chemokine receptors expression was evaluated by flow cytometry. sHLA-G downregulated expression of i) CCR2, CXCR3 and CXCR5 in CD4(+) T cells, ii) CXCR3 in CD8(+) T cells, iii) CXCR3 in Th1 clones iv) CXCR3 in TCR Vdelta2gamma9 T cells, and upregulated CXCR4 expression in TCR Vdelta2gamma9 T cells. sHLA-G inhibited in vitro chemotaxis of i) CD4(+) T cells towards CCL2, CCL8, CXCL10 and CXCL11, ii) CD8(+) T cells towards CXCL10 and CXCL11, iii) Th1 clones towards CXCL10, and iv) TCR Vdelta2gamma9 T cells towards CXCL10 and CXCL11. Downregulation of CXCR3 expression on CD4+ T cells by sHLA-G was partially reverted by adding a blocking antibody against ILT2/CD85j, a receptor for sHLA-G, suggesting that sHLA-G downregulated chemokine receptor expression mainly through the interaction with ILT2/CD85j. Follicular helper T cells (T(FH)) were isolated from human tonsils and stimulated as described above. sHLA-G impaired CXCR5 expression in T(FH) and chemotaxis of the latter cells towards CXCL13. Moreover, sHLA-G expression was detected in tonsils by immunohistochemistry, suggesting a role of sHLA-G in local control of T(FH) cell chemotaxis. Intracellular pathways were investigated by Western Blot analysis on total extracts from CD4+ T cells. Phosphorylation of Stat5, p70 s6k, beta-arrestin and SHP2 was modulated by sHLA-G treatment. Conclusions/significance Our data demonstrated that sHLA-G impairs expression and functionality of different chemokine receptors in T cells. These findings delineate a novel mechanism whereby sHLA-G modulates T cell recruitment in physiological and pathological conditions.